Characteristics of PRD1, a Plasmid-Dependent Broad Host Range DNA Bacteriophage - Olsen, Ronald H. (1974)
Several distinctive properties of PRD1, an icosahedral plasmid-dependent phage, are described. The drug-resistance plasmid-dependent host range of PRD1 extends beyond the P incompatibility group and includes gram-negative bacteria containing plasmids of incompatibility groups N and W. PRD1 phage will infect pseudomonads and Enterobacteriaceae containing either a P or W incompatibility group plasmid. PRD1 adsorbs to the cell wall of R(+) bacteria and thus its infectivity indicates cell wall alterations by these drug-resistance plasmid groups. PRD1 nucleic acid is duplex DNA with an estimated molecular weight of 24 × 10(6). The appearance of PRD1 in electron micrographs is suggestive of lipid content in addition to its buoyant density of 1.348 in CsCl and its sensitivity to chloroform. The latent period of PRD1 varies with the R(+) host bacterial strain used for growth of the phage.